Effects of Green Marketing Mix on Customer Satisfaction - Sah, Gunja Kumari (Khwopa Journal, 2025)
The research examines major influencing factors that can increase customer satisfaction. Data were gathered by convenience sampling from consumers of organic products. A structured questionnaire was prepared to collect data from respondents through emails and direct structured interviews with people who were directly met at the organic shop. For the primary data analysis, multicollinearity, normality test, and Durbin Watson autocorrelation have been carried out along with cross-checking of data to check the reliability and validity. The result showed that green price and green place was strongly correlated to each other and green product and green price moderately correlated. At last, it was found that green products and people were the most influential factors compared to other green marketing mix factors for customer satisfaction followed by place, physical evidence, and process. However, green prices and processes do not significantly influence customer satisfaction. This research provides information on green marketing mix to improve green business in Nepal.